Protocol for a meta-research study of protocols for diet or nutrition-related trials published in indexed journals: general aspects of study design, rationale and reporting limitations - Silva, FM; Adegboye, ARA; Curioni, C; Gomes, FS; Collins, GS; Kac, G; De Beyer, JA; Cook, JA; Cheikh Ismail, L; Page, MJ; Khandpur, N; Lamb, S; et al. (BMJ Publishing Group, 2022)
Introduction The Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) reporting guideline establishes a minimum set of items to be reported in any randomised controlled trial (RCT) protocol. The Template for Intervention Description and Replication (TIDieR) reporting guideline was developed to improve the reporting of interventions in RCT protocols and results papers. Reporting completeness in protocols of diet or nutrition-related RCTs has not been systematically investigated. We aim to identify published protocols of diet or nutrition-related RCTs, assess their reporting completeness and identify the main reporting limitations remaining in this field.